(untitled) - Atkins, Robert (New York, 1990)
Contents: The leading lexicon of contemporary art returns in an expanded, full-color third edition. An indispensable guide for art-world neophytes and seasoned professionals alike, the best-selling ArtSpeak returns in a revised and expanded third edition, illustrated in full color. Nearly 150 alphabetical entries-30 of them new to this edition-explain the who, what, where, and when of postwar and contemporary art. These concise mini-essays on the key terms of the art world are written with wit and common sense by veteran critic Robert Atkins. More than eighty images, most in color, illustrate key works of the art movements discussed, making ArtSpeak a visual reference, as well as a textual one. A timeline traces world and art-world events from 1945 to the present day, and a single-page ArtChart provides a handy overview of the major art movements in that period
Keywords: Art, Modern,Nghệ thuật, hiện đại; Dictionaries,Từ điển; 20th century,Thế kỷ 20